2019
DOI: 10.29333/ejmste/108437
|View full text |Cite
|
Sign up to set email alerts
|

Is the Future Bright? The Potential of Lightboard Videos for Student Achievement and Engagement in Learning

Abstract: Lightboard technology has only been around since 2013, but has already shown up on numerous campuses worldwide. There is a dearth of research related to lightboard videos, so there is a need to systematically explore its potential and best practices. This paper explores the pedagogical potential of lightboards for higher education through theoretical analysis and relevant literature evidence. Using relevant theoretical frameworks, including Cognitive Load Theory, Cognitive Theory of Multimedia Learning, and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…On the other hand, video animation also has several disadvantages, namely the large cost of production, requires a relatively long time from making, editing, until the video is useful, requires skill and creativity to package material and design animation. This is in line with the opinion expressed by Butcher (in Lubrick et al, 2019). He concluded that the diagram shown should not be more complicated than needed to communicate basic concepts.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, video animation also has several disadvantages, namely the large cost of production, requires a relatively long time from making, editing, until the video is useful, requires skill and creativity to package material and design animation. This is in line with the opinion expressed by Butcher (in Lubrick et al, 2019). He concluded that the diagram shown should not be more complicated than needed to communicate basic concepts.…”
Section: Introductionsupporting
confidence: 88%
“…One of the media that can be used in blended learning is animated video learning. Mayer (in Lubrick, Zhou, & Zhang, 2019) argues that individuals learn better through words and pictures compared to learning through pictures alone. It is clear that the animated video presents both words and pictures or diagrams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way how virtual lecturers can interact with dynamic visualizations is by creating them live during the lecture. Drawing information live instead of relating to already finalized and displayed information increases learners’ comprehension of the material (Lubrick et al 2019 ; Fiorella et al 2019 ). Viewing a lecturer that dynamically generates relevant information establishes a kind of social partnership between the learner and the instructor which, in turn, fosters generative processing of the material (Fiorella and Mayer 2016 ).…”
Section: Social Cues In Dynamic Learning Materialsmentioning
confidence: 99%
“…However, there is some encouraging evidence that the lightboard technology has potential to provide positive student experiences, consistent with evaluations from fields outside of engineering, 17 and prior studies have shown that lightboard-based videos are not likely to increase the cognitive load on students. 15 Finally, executing the development of this technology through a student-led capstone project places students in a unique position to positively impact the learning experiences of future students.…”
Section: Resultsmentioning
confidence: 99%